2016
DOI: 10.1002/2015wr018056
|View full text |Cite
|
Sign up to set email alerts
|

Response of the hyporheic zone to transient groundwater fluctuations on the annual and storm event time scales

Abstract: The volume of the water stored in and exchanged with the hyporheic zone is an important factor in stream metabolism and biogeochemical cycling. Previous studies have identified groundwater direction and magnitude as one key control on the volume of the hyporheic zone, suggesting that fluctuation in the riparian water table could induce large changes under certain seasonal conditions. In this study, we analyze the transient drivers that control the volume of the hyporheic zone by coupling the BrinkmanDarcy equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 58 publications
0
47
0
Order By: Relevance
“…While the model setup is based on site‐specific information and observations, it is not calibrated to the site. Rather, the model is heuristic; simulations were constructed to identify patterns in hyporheic flow path response due to different hydrologic boundary conditions and to test our hypothesis, which is consistent with common practice [e.g., Cardenas and Wilson , ; Gooseff et al ., ; Irvine and Lautz , ; Malzone et al ., ; Schmadel et al ., ; Trauth et al ., ]. Richards' equation was used to allow for groundwater flow simulations through the valley bottom for all possible hydrologic conditions ranging from a fully saturated subsurface to some locations of unsaturated subsurface [ Richards , ], xtrue[K(h)hxtrue]+ztrue[K(h)true(hz+1true)true]=0, where h ( x , z ) is the hydraulic head (m), x is the stream‐wise (down‐valley) direction (m), z is the vertical direction (m), and K ( h ) is the unsaturated hydraulic conductivity when h is less than the streambed elevation (m s −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the model setup is based on site‐specific information and observations, it is not calibrated to the site. Rather, the model is heuristic; simulations were constructed to identify patterns in hyporheic flow path response due to different hydrologic boundary conditions and to test our hypothesis, which is consistent with common practice [e.g., Cardenas and Wilson , ; Gooseff et al ., ; Irvine and Lautz , ; Malzone et al ., ; Schmadel et al ., ; Trauth et al ., ]. Richards' equation was used to allow for groundwater flow simulations through the valley bottom for all possible hydrologic conditions ranging from a fully saturated subsurface to some locations of unsaturated subsurface [ Richards , ], xtrue[K(h)hxtrue]+ztrue[K(h)true(hz+1true)true]=0, where h ( x , z ) is the hydraulic head (m), x is the stream‐wise (down‐valley) direction (m), z is the vertical direction (m), and K ( h ) is the unsaturated hydraulic conductivity when h is less than the streambed elevation (m s −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Momentum diffusion has been found to influence only the first ∼5 cm of the hyporheic zone depth [ Packman et al ., ]. Although an increase in the stream Reynolds number can increase the diffusion depth and possibly warrant a coupled Navier‐Stokes and Brinkman‐Darcy approach, most of the momentum still dissipates within a shallow depth, even during conditions of high stream turbulence [ Malzone et al ., ]. Therefore, the streambed boundary was set to hydrostatic head due to the water level relative to the streambed, and we ignore hydrodynamic contributions.…”
Section: Methodsmentioning
confidence: 99%
“…To validate the HPM, we test its performance in accurately predicting the OLs of flow paths using a series of numerical experiments. We constructed a 2‐D, vertically integrated (i.e., plan view) finite element model of groundwater transport through the hyporheic and riparian zone adjacent to a stream channel (Figure a), following similar model construction of past studies of hyporheic and riparian zones in COMSOL Multiphysics [ Schmadel et al ., ; Malzone et al ., ; Ward et al ., ]. The model domain was set to mimic the conditions of our field site in WS01 at the H.J.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown the importance of understanding the dynamic nature of river corridors (Boano et al, ; Dudley‐Southern & Binley, ; Gomez‐Velez et al, ; Malzone, Anseeuw, et al, ; Malzone, Lowry, et al, ; McCallum & Shanafield, ; Schmadel et al, ; Trauth & Fleckenstein, ; Ward et al, ; Ward et al, ) and identified dominant drivers and controls of hypoheic exchange flows during transient stream flow conditions. For example, Malzone, Lowry, et al () showed that the annual and storm‐induced groundwater fluctuations is the key control on the volume of HZ and Schmadel et al () highlighted the importance of controls such as hillslope lag, amplitude of the hillslope, and cross‐valley and down‐valley slopes on hyporheic flow path and residence times. McCallum and Shanafield () found alterations in the residence time distributions of bank inflows and outflows for different discharge events.…”
Section: Introductionmentioning
confidence: 99%